Community Capacity Assessment in Preventing Substance Abuse: A Participatory Approach - KH Shahandeh; R Majdzadeh; E Jamshidi; N Loori (Tehran University of Medical Sciences, 2012)
Background: Community-based participatory research (CBPR) increasingly is being used to address health issues. Few evidence exist to indicate how builds the capacity of communities to function as health promoter and what resources are required to promote successful efforts. This article presents the result of a capacity assessment for preventing drug abuse through CBPR, which working with rather than in communities, to strengthen a community's problem-solving capacity. For exploring the perception of stakeholders, a dynamic model of the dimensions of community and partnership capacity served as the theoretical framework. Methods: In this descriptive research, stakeholder analysis helps us to identify appropriate of stakeholders (Key stakeholders). Data were collected using a topic guide concerned with capacity for preventing drug abuse. Interviews were audiotape and transcribed. Data were analyzed thematically. Results: CBPR has been undertaken to involve local people in making decisions about the kind of change they want in their community and the allocation of resources to reduce substance abuse. We identified key stakeholders and examining their interests, resources and constraints of different stakeholders. Conclusion: The current study has shown the benefits of community-based participatory approach in assessing capacity. Through CBPR process people who affected by Drug issue engaged in analysis of their own situation and helps identity innovative solutions for their complex problem. This participatory approach to a capacity assessment resulted in a synergistic effort that provided a more accurate picture of community issues and concerns.